The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1093/oxfordjournals.eurheartj.a060473
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with unstable angina

Abstract: The aim of this study was to determine whether oxidative stress occurs in unstable angina. Thirty patients with unstable angina class B (Braunwald classification) were prospectively studied. Control groups consisted of 23 patients presenting with stable angina and of 21 age-matched healthy volunteers. Upon admission and every 8 h for 24 h, blood samples were drawn for the determination of plasma malondialdehyde (MDA) levels, Se-glutathione peroxidase (GPX) activity, erythrocyte reduced glutathione (GSH) concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 0 publications
5
29
1
Order By: Relevance
“…29) The current study observed a significant reduction in albumin, uric acid and total bilirubin and a significant increase in MDA, conjugated dienes and IscMA in AMI patients. The findings of the present study are similar to those of the study conducted by Dubois Rande et al 30) and Mc Murray 31) which reported a significant rise in MDA level and lipid peroxidation, with a concomitant decrease in antioxidants in patients with unstable angina and chronic heart failure. The present study also concurs with studies of Verma et al,32) who demonstrated that there was a significant drop in antioxidant, whereas lipid peroxides were significantly higher in AMI patients, compared with controls.…”
Section: Discussionsupporting
confidence: 92%
“…29) The current study observed a significant reduction in albumin, uric acid and total bilirubin and a significant increase in MDA, conjugated dienes and IscMA in AMI patients. The findings of the present study are similar to those of the study conducted by Dubois Rande et al 30) and Mc Murray 31) which reported a significant rise in MDA level and lipid peroxidation, with a concomitant decrease in antioxidants in patients with unstable angina and chronic heart failure. The present study also concurs with studies of Verma et al,32) who demonstrated that there was a significant drop in antioxidant, whereas lipid peroxides were significantly higher in AMI patients, compared with controls.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to work of Dubois Rande et al (17) and Mc Murray (18) who showed a decrease in antioxidant enzyme activities and increase in lipid peroxidation products (MDA, TBARS) in patients with unstable angina and chronic heart failure.…”
Section: Discussionsupporting
confidence: 91%
“…McMurray et al (29) and Dubois-Randé et al (49) similarly showed a decrease in antioxidant enzyme activities and increase in reaction oxygen products in patients with chronic heart failure and unstable angina, respectively. Although the antioxidant system (enzymatic/non-enzymatic) detoxifies ROS generated (17,30), an imbalance between the factors and tendency of lipid profiles to increase in CVD patients can be enhanced by oxidative stress.…”
Section: Mation (21)mentioning
confidence: 96%